Science Virtual Laboratory Implementation to Improve Students' Critical Thinking Skills: A Content Analysis - Risa Nurullailiyah Sujono; Maryati Maryati; Jumadi Jumadi (Postgraduate, University of Mataram, 2023)
Critical thinking skills are important for students to have for their future. One way to improve it is to apply virtual laboratory learning media to Science subjects. This study aims to analyze the implementation of virtual labs to improve students' critical thinking skills in science learning. This qualitative descriptive research uses content analysis study method. Researchers collect and classify various research results on the application of Virtual Laboratory (VL) from the S1-S3 Journal of Sinta using the PRISMA method and analyze them using a research instrument in the form of a Paper Classification Form (PCF). As a result, research on the use of virtual laboratories to improve students' critical thinking skills in science learning continues to increase from year to year, from high school to university levels. PhET and virtual labs developed by researchers when applied in class using inquiry models or STEM approaches or experimental methods have been proven to be able to effectively stimulate students to think critically